The Effect of Current Ratio, Debt to Equity Ratio and Liquidity on Dividend Policy for the Banking Sector Listed on the Indonesia Stock Exchange for the 2020-2024 Period - Nadila Agustina; Yusnia Betti Dame Marpaung; Tantri Octora Dwi Syah Putri; Zuwina Miraza (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the influence of the Current Ratio, Debt to Equity Ratio, and Liquidity on Corporate Dividend Policy in the banking sector, recorded on the IDX 2020–2024. The study uses a quantitative method with secondary data in the form of annual financial statements of banking corporations. The study sample was obtained using purposive sampling techniques from 21 corporations with a total of 105 observational data. Data analysis was carried out using multiple linear regression using IBM SPSS Statistics. The findings of the study show that the Dividend Policy is not significantly affected by the Current Ratio and Liquidity, while the Dividend Policy is significantly affected by the Debt to Equity Ratio. Dividend Policy is significantly affected together by the Current Ratio, Debt to Equity Ratio, and Liquidity. The Adjusted R Square value of 0.239 shows that independent variables can visualize the Dividend Policy of 23.9%, while the rest are influenced by other variables outside the study.